Modern Problems of the International Private Law as One of the Actual Directions of Students Research Activity - Alexandra V. Aleshina; Victoria A. Kosovskaya (Èkonomika, Pedagogika i Pravo, 2015)
In the present article authors features of discipline "The international private law" as necessary component of vocational training of lawyers come to light. Authors showed the difficult legal nature of the international private law, and also its dual character. In summary authors note that, most likely, in the near future experts in the field of the right won't develop the uniform concept concerning its nature that gives unlimited opportunities for scientific activities of students for research of actual problems of the international private law.